PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR SENI MUSIK SISWA KELAS V SDN 101765 BANDAR SETIA - Daniel Sinaga; Putra Afriadi; Elvi Mailani; Try Wahyu Purnomo; Syahrial (STKIP Subang, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Educaplay media on the music learning outcomes of fifth-grade students at SDN 101765 Bandar Setia. This research employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of 52 students divided into experimental and control classes, each with 26 students. Data collection techniques used multiple-choice tests. The results showed that the average post-test score of the experimental class was 79.04, higher than the control class at 70.77. Hypothesis testing using an independent sample t-test obtained a significance value (2-tailed) of 0.001 < 0.05, meaning H0 is rejected and Ha is accepted. Therefore, it is concluded that the TGT cooperative learning model assisted by Educaplay media significantly influences the music learning outcomes of fifth-grade students at SDN 101765 Bandar Setia.